2023
DOI: 10.36150/2499-6564-n613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combat sports on physical fitness and activities of daily living of older adults: a systematic review and meta-analysis of randomized controlled trials

Abstract: Pinheiro CJ, et al. Effect of combat sports on physical fitness and activities of daily living of older adults: a systematic review and meta-analysis of randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…A systematic review with meta-analysis conducted by Linhares, et al [28] reported significant improvements in favor of combat sports in static (p < 0.01) and dynamic balance (p < 0.01) compared to control groups in older people. In addition, individual results of the studies with OCS of a systematic review in older people by Valdés-Badilla, et al [22] reported improved physical measures (i.e., balance, muscle strength, and CRF), without being able to confirm the differences concerning control groups due to the diversity of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review with meta-analysis conducted by Linhares, et al [28] reported significant improvements in favor of combat sports in static (p < 0.01) and dynamic balance (p < 0.01) compared to control groups in older people. In addition, individual results of the studies with OCS of a systematic review in older people by Valdés-Badilla, et al [22] reported improved physical measures (i.e., balance, muscle strength, and CRF), without being able to confirm the differences concerning control groups due to the diversity of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Foram incluídos todos os ensaios clínicos publicados independente dos instrumentos de coleta de dados ou da data de publicação dos mesmos, desta forma a busca não foi restrita por período. Foram excluídos os ensaios clínicos que tratavam exclusivamente sobre o Tai Chi, por se tratar de uma prática em que já existem diversas revisões sistemáticas a respeito da sua eficácia clínica (Linhares et al, 2023;Hu et al, 2021;Wehner et al, 2021;Wang et al, 2020;Sherrington et al, 2019;Huang et al, 2017).…”
Section: Estudos Observacionais Comparativosunclassified